Profil Kemandirian Siswa SMA Berdasarkan Urutan Kelahiran dan Implikasinya Terhadap Bimbingan dan Konseling - Munggarani Ramadhan; Ipah Saripah (Indonesian Journal of Educational Counseling, 2017)
Autonomy Profile of Senior High School Student Based on Birth Order and Implication from Guidance and Counseling. The research was motivated by the lack of autonomy of students, where they so many factor influence which is birth order is among them. Autonomy is the readinnes of individuals to regulate, control, and manage themselves without depend on adult person and responnsibility for decision. The purpose of research to describe autonomy of students based on birth order. The research approach using a quantitative approach with descriptive method. The population in this reseacrh is a class XII student of SMA Al Muttaqin Fullday School Tasikmalaya Academic Year 2015/2016. The results showed a picture of autonomy of students based on birth order in higher category. Recommendations research showed to teachers Guidance and Counseling and further research.